Drug Delivery: Multifunctional Polymer‐Coated Carbon Nanotubes for Safe Drug Delivery (Part. Part. Syst. Charact. 4/2013). (22nd April 2013) - Moore, Thomas L.; Pitzer, Joshua E.; Podila, Ramakrishna; Wang, Xiaojia; Lewis, Robert L.; Grimes, Stuart W.; Wilson, James R.; Skjervold, Even; Brown, Jared M.; Rao, Apparao; Alexis, Frank
<x xml:space="preserve">Abstract</x> Poly(lactide)‐co‐poly(ethylene glycol) coated carbon nanotubes are used for controlled delivery of paclitaxel. Thomas Moore and co‐workers on page 365 report multifunctional polymer coated carbon nanotubes coated with biodegradable and biocompatible polymers to encapsulate and deliver drugs for a prolonged period of time. Furthermore, the coatings reduce in vitro cytotoxicity and in vivo systemic toxicity of carbon nanotubes, which is critical for intravenous administration. Image credit: Robert R. Johnson (University of Pennsylvania) <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>